Positive lead paste for lead storage battery and preparation method of positive lead paste

By using manganese dioxide/3D carbon-based composite electrode material to prepare lead paste, the problem of oxygen precipitation side reaction of the positive electrode plate of the lead battery is solved, the charging capacity and battery life are improved, and the energy density and cycle life are achieved. .

CN119208603APending Publication Date: 2024-12-27TIANNENG BATTERY GROUP

Patent Information

Application Number
CN202411099965.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-12
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The positive electrode plates of existing lead-acid batteries are prone to oxygen precipitation side reactions when charging, resulting in insufficient charging capacity and short service life. How to increase the oxygen evolution potential of the positive electrode plate and slow down polarization problems are urgently needed.

Method used

Manganese dioxide/3D carbon-based composite electrode material is used to replace traditional conductive graphite, and the lead paste is prepared by mixing with polytetrafluoroethylene emulsion, electrodeposition reaction and grinding, and combined with wet mixing method of dilute sulfuric acid and water to form a high conductivity and a positive lead paste with stable three-dimensional structure.

Benefits of technology

It improves the charging capacity of the positive electrode plate, reduces side reactions, extends the battery life, and improves the discharge capacity and energy density, and the charge and discharge efficiency reaches more than 95%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208603A_ABST
    Figure CN119208603A_ABST
Patent Text Reader

Abstract

The invention discloses positive lead paste for a lead storage battery and a preparation method of the positive lead paste. The formula of the positive lead paste comprises lead powder, dilute sulphuric acid, water and an additive, and the additive comprises the following components in parts by mass: 2-6 parts of manganese dioxide / three-dimensional carbon-based composite electrode material, 1-2 parts of antimony trioxide, 1-2 parts of stannous mono-sulphate, 20-50 parts of red lead and 0.8-1.2 parts of polyester fiber. The manganese dioxide / three-dimensional carbon-based composite electrode material is adopted to replace conductive graphite and other conductive carbon materials, the conductivity is good, a stable three-dimensional structure is achieved, the active substance structure can be fixed during discharging, the positive active substance is effectively prevented from being softened, and the service life of the battery is prolonged; manganese dioxide has an oxidation catalysis function and can catalyze the efficiency of converting lead sulfate into lead dioxide, so that the charging capacity of the positive plate is greatly improved during charging, and side reactions are reduced; the composite electrode material has high specific capacitance, and the discharge capacity of a positive plate is improved during discharge.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lead-acid batteries, and in particular relates to a positive lead paste for lead-acid batteries and a preparation method thereof. Background Art

[0002] Power lead-acid batteries are generally used in high-rate discharge cycles during use, and the use environment is complex and diverse. Ordinary people want electric vehicle batteries to be able to ride far, charge quickly, and have a long life. This puts higher demands on power lead-acid battery technology.

[0003] As we all know, the relationship between the life and capacity of lead-acid batteries is contradictory. The utilization rate of active materials is high, the initial capacity of the battery is high, but the service life is short. Therefore, how to increase the battery capacity while ensuring the battery service life is a problem that needs to be solved.

[0004] On the other hand, when the battery is charging, the positive plate is charged to about 70% of the discharge capacity, and the oxygen evolution side reaction begins to occur. The generated oxygen is compounded at the negative electrode to ensure the airtightness of the battery. Therefore, it is the positive electrode that truly determines the battery's charging acceptance capacity. How to increase the oxygen evolution potential of the positive plate or slow down the polarization problem of the positive plate during the charging reaction is also an urgent problem that needs to be solved.

[0005] In the prior art, conductive materials commonly used in positive electrode lead paste of lead-acid batteries include conductive graphite.

[0006] For example, the invention application with publication number CN117080370A discloses a positive electrode plate for a lead-acid battery, wherein the composition of the positive electrode lead paste includes lead powder, sulfuric acid solution, pure water and additives, with the weight of the lead powder being 100 parts, the sulfuric acid solution being 8.2 to 8.8 parts; the pure water being 10.0 to 11.0 parts; the additives including 0.2 to 0.4 parts of magnesium fluorosilicate solution, 0.08 to 0.10 parts of short fibers, 0.3 to 0.4 parts of colloidal graphite, 0.01 to 0.2 parts of antimony trioxide, and 0.25 to 0.3 parts of stannous sulfate; wherein the magnesium fluorosilicate solution is prepared by mixing and dissolving magnesium fluorosilicate crystals and pure water in a mass ratio of 1:1.

[0007] For another example, the invention application with publication number CN117855467A discloses a positive lead paste for a lead-acid battery, comprising lead powder and additives. Calculated by the mass of the positive lead paste, the additives include 0.3% to 2% calcium peroxide, 0.2% to 0.3% expanded graphite, 0.05% to 0.1% graphene, 0.8% to 1% tetrabasic lead sulfate, 0.1% to 0.3% metal sulfate, and 0.1% to 0.15% polyester staple fibers.

[0008] Conductive materials are very important to the performance of the positive electrode plate. Finding other conductive materials with better performance is expected to further improve the performance of lead-acid batteries. Summary of the invention

[0009] In view of the above-mentioned deficiencies in the prior art, the present invention provides a positive electrode lead paste for a lead-acid battery and a preparation method thereof.

[0010] A positive lead paste for a lead-acid battery comprises lead powder, dilute sulfuric acid, water and additives. The additives comprise 2 to 6 parts of manganese dioxide / three-dimensional carbon-based composite electrode material, 1 to 2 parts of antimony trioxide, 1 to 2 parts of stannous sulfate, 20 to 50 parts of red lead and 0.8 to 1.2 parts of polyester fiber per 1000 parts of lead powder.

[0011] Preferably, the manganese dioxide / three-dimensional carbon-based composite electrode material is composited with manganese dioxide and a conductive carbon material, and the preparation method of the manganese dioxide / three-dimensional carbon-based composite electrode material comprises the following steps: mixing the conductive carbon material with a polytetrafluoroethylene emulsion, pressing it into sheets, drying it to prepare a reaction electrode, inserting the reaction electrode into a potassium permanganate solution for an electrodeposition reaction, then taking out the reaction electrode, cleaning and air-drying it, and grinding it to obtain the manganese dioxide / three-dimensional carbon-based composite electrode material.

[0012] More preferably, the conductive carbon material and the polytetrafluoroethylene emulsion are mixed in a mass ratio of 90:10; the thickness of the reaction electrode is 0.5-1 mm; the concentration of the potassium permanganate solution is 1 mol / L; the temperature during the electrodeposition reaction is 60-80° C., the voltage is 1.2 V, and the time is 0.5-1 h.

[0013] More preferably, the conductive carbon material is at least one of carbon fiber, carbon nanotube and graphene.

[0014] Preferably, based on 1000 parts by mass of lead powder, the amount of dilute sulfuric acid is 90 to 100 parts, and the amount of water is 110 to 120 parts.

[0015] More preferably, the density of dilute sulfuric acid is 1.400 g / cm 3 .

[0016] The present invention further provides a method for preparing the positive lead paste for the lead-acid battery, comprising the following steps:

[0017] (1) Weigh each ingredient in the formula separately;

[0018] (2) Add the remaining additives except red lead into a paste mixer, then add red lead, and then add lead powder, and dry mix;

[0019] (3) adding the formulated amount of water for wet mixing;

[0020] (4) Add the formulated amount of dilute sulfuric acid for wet mixing.

[0021] Preferably, when water is added in step (3), it is added in multiple times, and stirring is performed after each addition; when dilute sulfuric acid is added in step (4), it is added in multiple times, and stirring is performed after each addition.

[0022] The present invention also provides a positive electrode plate of a lead-acid battery, comprising a positive electrode grid and a positive electrode lead paste, characterized in that the positive electrode lead paste uses the positive electrode lead paste for the lead-acid battery.

[0023] The present invention also provides a lead storage battery, comprising a positive electrode plate, and using the positive electrode plate.

[0024] The positive lead paste for the lead-acid battery of the present invention adopts manganese dioxide / three-dimensional carbon-based composite electrode material to replace conductive carbon materials such as conductive graphite, has good conductivity and a stable three-dimensional structure, can fix the structure of active substances when the battery is charged and discharged, effectively prevent the positive active substances from softening, and extend the battery life; manganese dioxide has an oxidation catalytic function, can catalyze the efficiency of converting lead sulfate into lead dioxide, greatly improves the charging capacity of the positive plate when the battery is charged, and reduces the occurrence of side reactions; the composite electrode material has a high specific capacitance, and improves the discharge capacity of the positive plate when the battery is discharged. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The discharge time and voltage curves of the battery assembled with the plates prepared with the positive plate lead paste of Examples 1, 2, 3 and Comparative Example 1 and the conventional negative plate. DETAILED DESCRIPTION

[0026] The content of the present invention will be described below in conjunction with specific examples. The following examples are tested using 6-DZF-20 product as a sample.

[0027] Example 1

[0028] Preparation of manganese dioxide / three-dimensional carbon-based composite electrode materials.

[0029] The carbon nanotube powder and PTFE (polytetrafluoroethylene) emulsion were mixed evenly at a mass ratio of 90:10, slurried, pressed into a 0.5 mm thick sheet, dried to make a reaction electrode, and inserted into a 1 mol / L potassium permanganate solution with a carbon fiber plate as a counter electrode, heated to 80°C, applied a working voltage of 1.2V, and the electrodeposition reaction was carried out for 0.5 hours. The reaction electrode was taken out, washed with water, naturally air-dried, and ground into powder to obtain a manganese dioxide / three-dimensional carbon-based composite electrode material obtained by compounding manganese dioxide and carbon nanotubes.

[0030] Example 2

[0031] Preparation of manganese dioxide / three-dimensional carbon-based composite electrode materials.

[0032] The carbon nanotube powder and PTFE (polytetrafluoroethylene) emulsion were mixed evenly at a mass ratio of 90:10, slurried, pressed into a 0.5 mm thick sheet, dried, and made into a reaction electrode. The carbon fiber plate was inserted into a 1 mol / L potassium permanganate solution as a counter electrode, heated to 70°C, and a working voltage of 1.2V was applied. The electrodeposition reaction was carried out for 0.5 hours. The reaction electrode was taken out, washed with water, naturally air-dried, and ground into powder to obtain a manganese dioxide / three-dimensional carbon-based composite electrode material obtained by compounding manganese dioxide and carbon nanotubes.

[0033] Example 3

[0034] Preparation of manganese dioxide / three-dimensional carbon-based composite electrode materials.

[0035] The carbon nanotube powder and PTFE (polytetrafluoroethylene) emulsion were mixed evenly at a mass ratio of 90:10, slurried, pressed into a 1mm thick sheet, dried to make a reaction electrode, and inserted into a 1mol / L potassium permanganate solution with a carbon fiber plate as a counter electrode, heated to 60°C, applied a working voltage of 1.2V, and the electrodeposition reaction was carried out for 1h. The reaction electrode was taken out, washed with water, naturally air-dried, and ground into powder to obtain a manganese dioxide / three-dimensional carbon-based composite electrode material obtained by compounding manganese dioxide and carbon nanotubes.

[0036] Example 4

[0037] A positive lead paste for a lead-acid battery uses the manganese dioxide / three-dimensional carbon-based composite electrode material prepared in Example 1.

[0038] The positive lead paste is prepared from the following components in parts by weight: 1000 parts of lead powder, dilute sulfuric acid (density 1.400 g / cm 3 (20°C)) 90 parts, deionized water 110 parts, auxiliary materials manganese dioxide / three-dimensional carbon-based composite electrode material 2 parts, antimony trioxide 1 part, stannous sulfate 1 part, red lead 40 parts, polyester fiber 0.8 parts.

[0039] The specific preparation steps of the lead paste are as follows:

[0040] Step 1: Accurately weigh the ingredients in each mass portion.

[0041] Step 2: Add the ingredients weighed in step 1 to the paste mixer, then add the formula amount of red lead, close the sealing cover of the paste mixer, and then accurately weigh the formula amount of lead powder through the lead powder delivery pipe of the paste mixer and add it to the paste mixer, and start mixing and stirring. Dry mix and stir for 5-8 minutes to make it evenly stirred.

[0042] Step 3: Add deionized water in the corresponding amount by mass of the embodiment three times, add 40% of the water within 1-3 minutes, stir for 1 minute, then add 20% of the water, stir for 1 minute, then add the remaining amount of water, and continue stirring for 4 minutes.

[0043] Step 4: Slowly add dilute sulfuric acid in three portions: Add 40% of dilute sulfuric acid within 6 minutes, stir for 1 minute, then add 20% of dilute sulfuric acid within 4 minutes, stir for 1 minute, then add the remaining amount of dilute sulfuric acid within 3 minutes, and continue stirring for 6 minutes.

[0044] Step 5: Measure the apparent specific gravity of the lead paste to be 4.40g / cm 3 Otherwise, use deionized water to adjust to the specified specific gravity.

[0045] The peak temperature of the entire lead paste preparation process is controlled below 75°C, and the paste outlet temperature is lower than 50°C.

[0046] Example 5

[0047] A positive electrode lead paste for a lead-acid battery uses the manganese dioxide / three-dimensional carbon-based composite electrode material prepared in Example 2.

[0048] The positive lead paste is prepared from the following components in parts by weight: 1000 parts of lead powder, dilute sulfuric acid (density 1.400 g / cm 3 (20°C)) 90 parts, deionized water 115 parts, auxiliary materials manganese dioxide / three-dimensional carbon-based composite electrode material 4 parts, antimony trioxide 2 parts, stannous sulfate 2 parts, red lead 20 parts, polyester fiber 1 part.

[0049] The specific preparation steps of the lead paste are as follows:

[0050] Step 1: Accurately weigh each ingredient by mass.

[0051] Step 2: Add the ingredients weighed in step 1 to the paste mixer, then add the formula amount of red lead, close the sealing cover of the paste mixer, and then accurately weigh the formula amount of lead powder through the lead powder delivery pipe of the paste mixer and add it to the paste mixer, and start mixing and stirring. Dry mix and stir for 5 minutes to make it evenly stirred.

[0052] Step 3: Add deionized water in the corresponding amount by mass of the embodiment three times: add 40% of the water within 1 minute, stir for 1 minute, then add 20% of the water, stir for 1 minute, then add the remaining amount of water, and continue stirring for 4 minutes.

[0053] Step 4: Slowly add dilute sulfuric acid in three times: Add 40% dilute sulfuric acid within 6 minutes, stir for 1 minute, then add 20% dilute sulfuric acid within 4 minutes, stir for 1 minute, then add the remaining amount of dilute sulfuric acid within 3 minutes, and continue stirring for 6 minutes.

[0054] Step 5: Measure the apparent specific gravity of the lead paste to be 4.40g / cm 3 Otherwise, use deionized water to adjust to the specified specific gravity.

[0055] The peak temperature of the entire lead paste preparation process is controlled below 75°C, and the paste outlet temperature is lower than 50°C.

[0056] Example 6

[0057] A positive lead paste for a lead-acid battery uses the manganese dioxide / three-dimensional carbon-based composite electrode material prepared in Example 3.

[0058] The positive lead paste is prepared from the following components in parts by weight: 1000 parts of lead powder, dilute sulfuric acid (density 1.400 g / cm 3 (20°C)) 100 parts, deionized water 120 parts, auxiliary materials manganese dioxide / three-dimensional carbon-based composite electrode material 6 parts, antimony trioxide 2 parts, stannous sulfate 2 parts, red lead 50 parts, polyester fiber 1.2 parts.

[0059] The specific preparation steps of the lead paste are as follows:

[0060] Step 1: Accurately weigh each ingredient by mass.

[0061] Step 2: Add the ingredients weighed in step 1 to the paste mixer, add the formula amount of red lead, close the sealing cover of the paste mixer, and then accurately weigh the formula amount of lead powder through the lead powder delivery pipe of the paste mixer and add it to the paste mixer, and start mixing and stirring. Dry mix and stir for 8 minutes to make it evenly stirred.

[0062] Step 3: Add deionized water in the corresponding amount by mass of the embodiment three times, add 60% of the water within 3 minutes, stir for 2 minutes, then add 30% of the water, stir for 2 minutes, then add the remaining amount of water, and continue stirring for 8 minutes.

[0063] Step 4: Slowly add dilute sulfuric acid in three times: Add 60% of dilute sulfuric acid within 10 minutes, stir for 2 minutes, then add 30% of dilute sulfuric acid within 8 minutes, stir for 2 minutes, then add the remaining amount of dilute sulfuric acid within 6 minutes, and continue stirring for 15 minutes.

[0064] Step 5: Measure the apparent specific gravity of the lead paste to be 4.50g / cm 3 Otherwise, use deionized water to adjust to the specified specific gravity.

[0065] The peak temperature of the entire lead paste preparation process is controlled below 75°C, and the paste outlet temperature is lower than 50°C.

[0066] Comparative Example 1

[0067] The positive lead paste is prepared from the following components in parts by weight: 1000 parts of lead powder, dilute sulfuric acid (density 1.400 g / cm 3(20°C)) 90 parts, deionized water 110 parts, auxiliary materials conductive graphite 2 parts, antimony trioxide 1 part, stannous sulfate 1 part, red lead 40 parts, polyester fiber 0.8 parts.

[0068] The specific preparation steps of the lead paste are as follows:

[0069] Step 1: Accurately weigh each ingredient by mass.

[0070] Step 2: Add the ingredients weighed in step 1 to the paste mixer, then add the formula amount of red lead, close the sealing cover of the paste mixer, and then accurately weigh the formula amount of lead powder through the lead powder delivery pipe of the paste mixer and add it to the paste mixer, and start mixing and stirring. Dry mix and stir for 5 minutes to make it evenly stirred.

[0071] Step 3: Add deionized water in the corresponding amount by mass of the embodiment three times: add 40% of the water within 1 minute, stir for 1 minute, then add 20% of the water, stir for 1 minute, then add the remaining amount of water, and continue stirring for 4 minutes.

[0072] Step 4: Slowly add dilute sulfuric acid in three portions: Add 40% of dilute sulfuric acid within 6 minutes, stir for 1 minute, then add 20% of dilute sulfuric acid within 4 minutes, stir for 1 minute, then add the remaining amount of dilute sulfuric acid within 3 minutes, and continue stirring for 6 minutes.

[0073] Step 5: Measure the apparent specific gravity of the lead paste to be 4.40g / cm 3 Otherwise, use deionized water to adjust to the specified specific gravity.

[0074] The peak temperature of the entire lead paste preparation process is controlled below 75°C, and the paste outlet temperature is lower than 50°C.

[0075] Test Example 1

[0076] Referring to the method disclosed in Chinese patent document CN110247024B, the lead pastes prepared in Examples 4 to 6 and Comparative Example 1 were made into power lead-acid batteries, and then the batteries were tested according to the method of Chinese patent document CN110247024B. The test results are as follows (6-DZF-20 battery): Table 1 and Figure 1 (2hr discharge time) as shown.

[0077] Table 1

[0078] project Example 4 Example 5 Example 6 Comparative Example 1 2hr discharge time / min 128.5 130.4 131.2 120.7 2hr discharge capacity / Ah 21.74 22.05 22.2 20.4 -18℃ low temperature capacity / Ah 14.6 14.5 14.7 14.5 Charging acceptance 2.6 2.8 2.9 2.4 High current discharge capability / min 32.4 35.1 36.3 27.3 Fast charging capability 1.02 1.04 1.04 0.99 Energy densityWh / kg 43.5 44.1 44.4 40.8 Cycle life / number of times 450 492 551 410 Cycle energy efficiency / % 95 95 96 89

[0079] Comparing the above test results, the embodiments of the present invention have the following improvements:

[0080] 1. The utilization rate of battery active materials is improved, and the initial capacity is increased by more than 6% and the specific energy density is increased by more than 7% compared with the comparative example.

[0081] 2. The charging acceptance capacity is increased by 8%-20% compared with the comparison ratio, the fast charging capacity reaches above 1.02, and the charging and discharging energy efficiency reaches more than 95% during the cycle life cycle.

[0082] 3. The battery cycle life is increased by 10%-30% compared with the control ratio.

Claims

1. A positive lead paste for a lead-acid battery, comprising lead powder, dilute sulfuric acid, water and an additive, characterized in that: Based on 1000 parts of lead powder, the additives include: 2-6 parts of manganese dioxide / three-dimensional carbon-based composite electrode material, 1-2 parts of antimony trioxide, 1-2 parts of stannous sulfate, 20-50 parts of red lead, and 0.8-1.2 parts of polyester fiber.

2. The positive electrode lead paste for a lead-acid battery according to claim 1, characterized in that: The manganese dioxide / three-dimensional carbon-based composite electrode material is composited with manganese dioxide and a conductive carbon material. The preparation method of the manganese dioxide / three-dimensional carbon-based composite electrode material comprises the following steps: The conductive carbon material is mixed with polytetrafluoroethylene emulsion, pressed into sheets, and dried to prepare a reaction electrode. The reaction electrode is inserted into a potassium permanganate solution for electrodeposition reaction. The reaction electrode is then taken out, cleaned, air-dried, and ground to obtain the manganese dioxide / three-dimensional carbon-based composite electrode material.

3. The positive electrode lead paste for lead-acid battery according to claim 2, characterized in that: The conductive carbon material and the polytetrafluoroethylene emulsion are mixed in a mass ratio of 90:10; the thickness of the reaction electrode is 0.5-1 mm; the concentration of the potassium permanganate solution is 1 mol / L; the temperature during the electrodeposition reaction is 60-80° C., the voltage is 1.2 V, and the time is 0.5-1 h.

4. The positive electrode lead paste for a lead-acid battery according to claim 2, characterized in that: The conductive carbon material is at least one of carbon fiber, carbon nanotube and graphene.

5. The positive electrode lead paste for lead-acid battery according to claim 1, characterized in that: Based on 1000 parts of lead powder, the amount of dilute sulfuric acid is 90-100 parts, and the amount of water is 110-120 parts.

6. The positive electrode lead paste for lead-acid battery according to claim 5, characterized in that: The density of dilute sulfuric acid is 1.400 g / cm 3 .

7. The method for preparing the positive electrode lead paste for lead-acid batteries according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) Weigh each ingredient in the formula separately; (2) Add the remaining additives except red lead into a paste mixer, then add red lead, and then add lead powder, and dry mix; (3) adding the formulated amount of water for wet mixing; (4) Add the formulated amount of dilute sulfuric acid for wet mixing.

8. The preparation method according to claim 7, characterized in that: When adding water in step (3), add it in multiple times and stir after each addition; when adding dilute sulfuric acid in step (4), add it in multiple times and stir after each addition.

9. A positive plate of a lead-acid battery, comprising a positive plate grid and a positive lead paste, characterized in that: The positive electrode paste is the positive electrode paste for a lead-acid battery according to any one of claims 1 to 6.

10. A lead-acid battery comprising a positive plate, characterized in that: Use the positive electrode plate described in claim 9.

Citation Information

Patent Citations

  • A formula for lead paste for storage battery plates and a method for preparing storage battery plates.

    CN110247024B

  • Positive plate of lead storage battery and lead storage battery

    CN117080370A

  • Positive lead paste of lead storage battery and preparation method of positive lead paste

    CN117855467A

Cited By

  • Preparation method and application of high-specific-capacitance lead storage battery positive electrode lead paste

    CN120109165A

  • Preparation method and application of high specific capacitance lead-acid battery positive electrode lead paste

    CN120109165B

  • Positive electrode carbon-enhanced and negative electrode fully-carbonized electrode and preparation process of positive electrode carbon-enhanced and negative electrode fully-carbonized electrode

    CN121035159A